Analysis of Prostate-Specific Antigen Transcripts in Chimpanzees, Cynomolgus Monkeys, Baboons, and African Green Monkeys - Mubiru, James N.; Yang, Alice S.; Olsen, Christian; Nayak, Sudhir; Livi, Carolina B.; Dick Jr., Edward J.; Owston, Michael; Garcia-Forey, Magdalena; Shade, Robert E.; Rogers, Jeffrey (PLoS One, 2014)
The function of prostate-specific antigen (PSA) is to liquefy the semen coagulum so that the released sperm can fuse with the ovum. Fifteen spliced variants of the PSA gene have been reported in humans, but little is known about alternative splicing in nonhuman primates. Positive selection has been reported in sex- and reproductive-related genes from sea urchins to Drosophila to humans; however, there are few studies of adaptive evolution of the PSA gene. Here, using polymerase chain reaction (PCR) product cloning and sequencing, we study PSA transcript variant heterogeneity in the prostates of chimpanzees (Pan troglodytes), cynomolgus monkeys (Macaca fascicularis), baboons (Papio hamadryas anubis), and African green monkeys (Chlorocebus aethiops). Six PSA variants were identified in the chimpanzee prostate, but only two variants were found in cynomolgus monkeys, baboons, and African green monkeys. In the chimpanzee the full-length transcript is expressed at the same magnitude as the transcripts that retain intron 3. We have found previously unidentified splice variants of the PSA gene, some of which might be linked to disease conditions. Selection on the PSA gene was studied in 11 primate species by computational methods using the sequences reported here for African green monkey, cynomolgus monkey, baboon, and chimpanzee and other sequences available in public databases. A codon-based analysis (dN/dS) of the PSA gene identified potential adaptive evolution at five residue sites (Arg45, Lys70, Gln144, Pro189, and Thr203).
Keywords: Prostate; Transcripts; Chimpanzees; Cynomolgus Monkeys; Baboons; African Green Monkeys